PENANGGULANGAN KEMISKINAN DALAM KONSEP AL-QURAN - Rosnani Siregar (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Because thre are many factor leading people to poverty, it cannotbe eliminated completely without taking the factor into consideration .one of them is laziness resulted from an envirovment morever.There is aperson who has sacha character of laziness. Islam a religion encouragingits flowers to be rich, motivates people to work hard,thas, Islam obligewealting people to help the needies to enhace their economy Islampoundes same conseft to help them, they are mudharabah, ijarah, andariyah.